2004
DOI: 10.1002/chem.200400220
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Phenanthrenes and Polycyclic Heteroarenes by Transition‐Metal Catalyzed Cycloisomerization Reactions

Abstract: Readily available biphenyl derivatives containing an alkyne unit at one of their ortho-positions are converted into substituted phenanthrenes on exposure to catalytic amounts of either PtCl2, AuCl, AuCl3, GaCl3 or InCl3 in toluene. This 6-endo-dig cyclization likely proceeds through initial pi-complexation of the alkyne unit followed by interception of the resulting eta2-metal species by the adjacent arene ring. The reaction is inherently modular, allowing for substantial structural variations and for the inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
260
2
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 623 publications
(276 citation statements)
references
References 235 publications
10
260
2
4
Order By: Relevance
“…When PtCl 2 is used instead of PtCl 4 , the yield decreases (29%). This result is conform to others described in the literature [23]. Howover, Federov and al showed that the intramolecular hydroarylation can be obtained in higher yield (60-91%) using catalytic amount of Pd(OAc) 2 [24].…”
Section: Resultssupporting
confidence: 92%
“…When PtCl 2 is used instead of PtCl 4 , the yield decreases (29%). This result is conform to others described in the literature [23]. Howover, Federov and al showed that the intramolecular hydroarylation can be obtained in higher yield (60-91%) using catalytic amount of Pd(OAc) 2 [24].…”
Section: Resultssupporting
confidence: 92%
“…3). 26,123 The authors also propose a vinylidene intermediate for this transformation, which was initially supported by a teorethical analysis. 28 Nevertheless, later computational studies have demonstrated that a mechanism consisting in a 6-endo cyclization followed by consecutive 1,2-H/1,2-halo migrations cannot be ruled out.…”
Section: Ethynylbenzenes and Azidesmentioning
confidence: 87%
“…Thed isparity in reaction outcome between BCl 3 (borylative cyclization) and GaCl 3 (cycloisomerization) is again noteworthy. [22] Theb orylative cyclization of 2-alkynyl-1,1'-biphenyls forms versatile intermediates (e.g., 6)w hich can be transformed into desirable materials,s uch as dibenzochrysenes by established methodologies. [23] Them ore functionality-rich precursor 7, containing ah eteroaromatic, ab romide,a nd ah exyl-substituted alkyne,was also amenable to borylative cyclization and delivered 8 in 58 %y ield.…”
Section: Methodsmentioning
confidence: 99%